2012
DOI: 10.1111/pace.12006
|View full text |Cite
|
Sign up to set email alerts
|

Low Body Mass Index Is Associated with a Positive Response during a Head‐Up Tilt Test

Abstract: In our sample, changes in BMI are associated with a positive response for HUT, and oral contraceptives seemed to protect against this response. Further studies are needed with larger numbers of patients to corroborate this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In obesity, chronic caloric surplus raises sympathetic activity and blood pressure [14] while improving orthostatic tolerance [24]. Chronic caloric deficiency elicits the opposite response in individuals with low body mass index and in patients with anorexia nervosa [17,23]. A few days of caloric restriction are sufficient in reducing sympathetic outflow and orthostatic tolerance in both obese and lean individuals [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…In obesity, chronic caloric surplus raises sympathetic activity and blood pressure [14] while improving orthostatic tolerance [24]. Chronic caloric deficiency elicits the opposite response in individuals with low body mass index and in patients with anorexia nervosa [17,23]. A few days of caloric restriction are sufficient in reducing sympathetic outflow and orthostatic tolerance in both obese and lean individuals [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The patients in this study had a history of syncope and a lower BMI compared to the healthy group, and both groups were within normal weight ranges. Greater incidence of syncope related to lower BMI has been reported; Luis Luz Leira et al (15) in a study of 419 patients undergoing head-up tilt test for syncope investigation reported a higher incidence of a positive test in those with BMI values < 18.5 kg/m2 (p=0.01). Other studies indicate that body weight influences the response to orthostatism, which could be a factor influencing both the history of syncope and the symptomatic response during the test.…”
Section: Discussionmentioning
confidence: 95%
“…Individuals with lower BMI have greater predisposition to vasovagal syncope and orthostatic hypotension, often accompanied by dysregulated autonomic nervous system activity. 26–28 …”
Section: Discussionmentioning
confidence: 99%
“…Individuals with lower BMI have greater predisposition to vasovagal syncope and orthostatic hypotension, often accompanied by dysregulated autonomic nervous system activity. [26][27][28] LVEF is a valuable indicator for the diagnosis and monitoring of heart conditions such as heart failure and cardiomyopathy. Our findings have demonstrated that LVEF was an independent predictor to discriminate cardiac syncope from non-cardiac syncope.…”
mentioning
confidence: 99%